Evaluation of Helical Pile Performance in TRcM for Soft Ground Improvement: Insights from Field Test and Application - Kim Hyeong-Joo; Ham Tae-Gew; Shamsher Sadiq; Peter Rey Dinoy; Youn Gi-Cheol (Advances in Civil Engineering)
The tabular roof construction method (TRcM) is an alternative to open-cut and cover tunnels commonly used in constructing underground structures. The open-cut tunnels often lead to traffic congestion and ground settlement, especially in densely populated areas. However, when dealing with very soft ground that allows minimal settlement, piling becomes necessary to distribute the load. Implementing ground improvement solutions in such scenarios poses challenges in terms of space and time constraints. This study presents a unique case study that explores the combination of helical piles with the TRcM, offering a viable solution for ground improvement under challenging ground, limited space, and time constraint conditions. A robust helical pile loading system design for static compression tests inside TRcM ensuring TRcM pipe stability is presented. Also, the validation of the helical pile-bearing capacity interpretation using various factors through static field test inside the TRcM is presented.